(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the transformation of archaisms in the Turkic written monuments, as well as their variations in terms of the modern Turkic languages. Several changes in the ancient roots of the Kazakh language are stated. Such changes include the removal of some vowels, consonants; transformation of rounded sounds into unrounded and the voiceless into voiced consonants. The author notes that forms such as qakpug, qapyg, qapy, qabyq, qaqpa, qap (қапуғ, қапағ, қапығ, қапы, қабық, қақпа, қап) are formed from one root «qap» («қап»). «қap.» Features of development of such forms as tugur> tugul> togul> ogul; tugush> togush> ogush (туғур >туғул>тоғул >оғул; туғуш>тоғуш>оғуш) in the Oguz language and forms of Kipchak language such as tugur> tugul> ugul> uul> ul; tugus> tugys> tuys (туғур>туғул>уғул>уул>ұл; туғус>туғыс>туыс) are explained as well. One omitted sound in these words is capable to transform the word unrecognizably. This phenomenon has turned the previously words into archaisms. The examples presented in the article were taken from the materials of the ancient Turkic manuscripts and related Turkic languages.